1991
DOI: 10.2307/280974
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Investigation of Biocultural Relationships among Three Late Prehistoric Societies in Tennessee

Abstract: Interrelations among three roughly contemporaneous late prehistoric Mississippian societies in Middle and East Tennessee are reexamined in terms of currently available biological, archaeological, and ethnohistoric data. Previous researchers have suggested a close relation between two of those cultures—Mouse Creek and Middle Cumberland—to the exclusion of the third, Dallas. However, multivariate analyses of craniofacial and mandibular dimensions of individuals from the three groups suggest a greater biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Additionally, the results of this study indicate no evidence for differences in activity among subadults between the regions, though without cross‐sectional properties this cannot be definitively ascertained. In contrast, Boyd and Boyd () found the adult population from Averbuch to be biologically distinct from individuals from the East Tennessee Mouse Creek Phase sites of Ledford Island, Mouse Creek, and Rymer, as well as the Dallas Phase sites of Dallas and Toqua. Perhaps there is a degree of catch‐up growth and bone remodeling that is occurring in the later stages of adolescence that this study is not catching.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, the results of this study indicate no evidence for differences in activity among subadults between the regions, though without cross‐sectional properties this cannot be definitively ascertained. In contrast, Boyd and Boyd () found the adult population from Averbuch to be biologically distinct from individuals from the East Tennessee Mouse Creek Phase sites of Ledford Island, Mouse Creek, and Rymer, as well as the Dallas Phase sites of Dallas and Toqua. Perhaps there is a degree of catch‐up growth and bone remodeling that is occurring in the later stages of adolescence that this study is not catching.…”
Section: Discussionmentioning
confidence: 94%
“…Whether these events were causally related between the two regions remains unresolved. Previous biological distance studies comparing adults from both Dallas and Mouse Creek Phase sites have found no biological differences (Boyd, ; Boyd & Boyd, ; Harle, ; King, ; McCarthy, ; Vidoli, ). Thus, the analyses herein seek to add to the growing body of biological evidence for late Mississippian Period changes among groups in Tennessee.…”
Section: Introductionmentioning
confidence: 86%
“…At the time of European contact the mortuary program of native peoples of the Southeast and Atlantic seaboard varied enormously. Corpse disposal included primary inhumation (in flexed, semi-flexed and extended positions) within plazas, in mounds, in stone box graves, or under house floors, as well as the use of charnel houses, typically with corpse defleshing and then secondary bundle burial within accretional mounds (Boyd and Boyd 1991;Dunham et al 2003;Gold 2000Gold , 2004Johnson et al 1994;Reeves 2000, pp. 81-82;Speck 1939;Stojanowski 2010, p. 118;Sullivan and Harle 2010).…”
Section: Discussionmentioning
confidence: 99%
“…strategically positioned in the hinterlands and bluff tops, affording maximum visibility of the land below to spot rival groups (Worne et al, 2012). Notably, a palisade was constructed over Averbuch's oldest cemetery, late in the site's occupation; there is evidence that this construction may have been done hastily as a means of defense, in an attempt to persevere despite deteriorating cultural and environ- Boyd & Boyd, 1991;Schroedl, 1998), MCR groups could have made contact with geographically disparate groups.…”
Section: Notementioning
confidence: 99%